Effects of embryo injected with ochratoxins A on hatching quality and jejunum antioxidant capacity of ducks at hatching - Liu, Jinhui; Jiang, Xiayu; Peng, Xin; Yuan, Yihan; Shen, Yu; Li, Yongxia; Yan, Zixing; Yuan, Xi; Yang, Ye; Zhai, Shuangshuang (Frontiers in Veterinary Science, 2022)
Numerous studies have shown that ochratoxins-A (OTA) exerts diverse toxicological effects, including hepatotoxicity, nephrotoxicity, genotoxicity, enterotoxicity and immunotoxicity. The main objective of this study was to investigate the influence of embryonic exposure to OTA by different injection time and OTA doses on hatching quality and jejunal antioxidant capacity of ducks at hatching. Four hundred and eighty fertilized eggs were weighed and randomly assigned into a 4×4 factorial design including four OTA doses (0, 2, 4, 8 ng/g egg) on 8, 13, 18, 23 of embryonic development (E8, E13, E18 and E23). Each treatment included 6 repeats with 5 eggs per repeat. The results showed that the injection time affected the hatching weight (P<0.0001). The relative length of the jejunum and ileum on E18 and E23 was lower than E8 and E13 (P<0.05). Injection time, doses and their interaction had no effect on jejunum morphology, including villous height (Vh), crypt depth (Cd) and villous height/crypt depth ratio Vh/Cd (P>0.05). The injection time affected the activities of Superoxide dismutase (SOD) (P<0.0001), total antioxidant capacity (T-AOC) (P<0.05) and the malondialdehyde (MDA) content (P<0.0001). The activity of SOD and T-AOC activities in jejunum of ducklings injected with OTA at the E8 and E13 was lower than that injected at the E18 (P<0.05). The highest MDA content was observed in ducklings injected with OTA at the E13 (P<0.05). The injection time (P<0.0001), OTA doses and their interaction affected the contents of IL-1β (P<0.05), which significantly increased especially on E13. In conclusion, embryo injected with ochratoxins A affected the hatching weight, the relative length of jejunum and ileum, decreased the antioxidant capacity and increased the content of proinflammatory cytokine IL-1β of jejunum.